2011
DOI: 10.1111/j.1600-0714.2011.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of stromal inflammation in squamous cell carcinoma of the tongue

Abstract: Data clearly showed that tongue tumours have a split invasive growth pattern and an intense inflammatory response at the tumour interface. Results also indicated that evaluation of the intensity of the inflammatory infiltrate at the tumour interface in tongue SCC could provide information of potential importance for choice of treatment and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 13 publications
(15 reference statements)
3
28
1
Order By: Relevance
“…For tongue carcinoma, no specific prognostic factors have been found. Concerning prognosis, our own previous results of tongue tumours showed that evaluation of the inflammatory infiltrate at the tumour interface could give potentially valuable information for choice of treatment and prognosis . We also found a significantly higher frequency of recurrence in young compared to old patients .…”
Section: Introductionsupporting
confidence: 55%
“…For tongue carcinoma, no specific prognostic factors have been found. Concerning prognosis, our own previous results of tongue tumours showed that evaluation of the inflammatory infiltrate at the tumour interface could give potentially valuable information for choice of treatment and prognosis . We also found a significantly higher frequency of recurrence in young compared to old patients .…”
Section: Introductionsupporting
confidence: 55%
“…A recent study on oral tongue SCC did not find any correlation of WPOI with prognosis or response to treatment, but a dense LHR was associated with complete response to therapy. This latter study comprised all stages of oral tongue SCC, in addition to using only biopsy specimens . These 2 factors may have influenced their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics are shown in Table . Tissue biopsies had been consecutively collected and some patients were included in our previous studies with different objectives . Biopsies taken from the lateral border of the tongue from 14 healthy volunteers not exposed to classic oral cancer risk factors (smoking and alcohol) had also been collected previously .…”
Section: Methodsmentioning
confidence: 99%